2023
DOI: 10.1002/cam4.6242
|View full text |Cite
|
Sign up to set email alerts
|

YAP/STAT3 inhibited CD8+ T cells activity in the breast cancer immune microenvironment by inducing M2 polarization of tumor‐associated macrophages

Abstract: BackgroundBreast cancer (BC) is the leading cause of cancer‐related death among women. One of the hallmarks of cancer is sustained angiogenesis. YAP/STAT3 may promote angiogenesis and driving BC progression. This study aimed to investigate how YAP/STAT3 affects the immune microenvironment in BC and understand the underlying mechanism.MethodsTo establish a tumor‐associated macrophages (TAMs) model, macrophages were cultured in the 4T1 cell culture medium. A BC mouse model was created by injecting 4T1 cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In another study, low ECM protein expression and reduced YAP activation were accompanied by an increase in M1 macrophages, showing a favorable clinical prognosis in uterine sarcomas [ 81 ]. In stiff breast cancer tissue, YAP also induces macrophage M2 polarization and subsequently inhibits CD8 + T-cell activity and promotes tumor progression [ 82 ]. Furthermore, macrophage M2 polarization was increased in colorectal cancer by activating the Rho/Hippo/YAP signaling pathway [ 83 ].…”
Section: Matrix Stiffness Regulates Macrophage Polarization Through M...mentioning
confidence: 99%
“…In another study, low ECM protein expression and reduced YAP activation were accompanied by an increase in M1 macrophages, showing a favorable clinical prognosis in uterine sarcomas [ 81 ]. In stiff breast cancer tissue, YAP also induces macrophage M2 polarization and subsequently inhibits CD8 + T-cell activity and promotes tumor progression [ 82 ]. Furthermore, macrophage M2 polarization was increased in colorectal cancer by activating the Rho/Hippo/YAP signaling pathway [ 83 ].…”
Section: Matrix Stiffness Regulates Macrophage Polarization Through M...mentioning
confidence: 99%
“…Targeting the Hippo signalling pathway is also a possibility for treatment. Another study found that the interaction between hippo-yes-associated protein (YAP) and signal transducer and activator of transcription 3 (STAT3) are highly expressed in breast cancer tissues, leading to an increase in macrophage polarization towards the M2 type [22] (Fig. 1).…”
Section: Repolarization Of Macrophagesmentioning
confidence: 99%